Auxin‐Inducible Degron System for Depletion of Proteins in Saccharomyces cerevisiae. Issue 1 (6th September 2019) - Shetty, Ameet; Reim, Natalia I.; Winston, Fred
Abstract: The auxin‐inducible degron (AID) is a powerful tool that is used for depletion of proteins to study their function in vivo. This method can conditionally induce the degradation of any protein by the proteasome simply by the addition of the plant hormone auxin. This approach is particularly valuable to study the function of essential proteins. The protocols provided here describe the steps to construct the necessary strains and to optimize auxin‐inducible depletion in Saccharomyces cerevisiae . © 2019 by John Wiley & Sons, Inc. Basic Protocol 1 : Construction of TIR1‐expressing strains by transformation Basic Protocol 2 : Tagging a yeast protein of interest with an auxin‐inducible degron Support Protocol : Construction of depletion strains by genetic crosses Basic Protocol 3 : Optimization for depletion of the auxin‐inducible‐degron‐tagged protein